Exploratory Study on the Linux OS Jitter - Vicente, Elder; Matias Jr., Rivalino (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
The operating system (OS) Jitter phenomenon has been considered an import and critical factor in high-performance distributed computing. In this paper, we present the results of an experimental study that quantifies the effects of different sources of OS Jitter in the Linux operating system. We use the design of experiments (DOE) method to conduct controlled experiments statistically planned. Different than previous studies, we found that the processor topology, especially regarding the shared processor cache, has the most significant influence in terms of OS Jitter. Also, we found that in order to reduce the impact of OS Jitter on a given application, the number of computational phases in the algorithm is significantly more important than the number of distributed processes or compute nodes.